2011
DOI: 10.1063/1.3571561
|View full text |Cite
|
Sign up to set email alerts
|

Robust gigahertz fiber quantum key distribution

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…A widely-available, high-throughput, low-latency TRNG will enable all previously mentioned applications that rely on TRNGs, including improved security and privacy in most systems that are known to be vulnerable to attacks [90,115,162], as well as enable research that we may not anticipate at the moment. One such direction is using a one-time pad (i.e., a private key used to encode and decode only a single message) with quantum key distribution, which requires at least 4Gb/s of true random number generation throughput [34,94,154]. Many high-throughput TRNGs have been recently proposed [12,15,31,42,48,80,82,101,110,147,154,159,162,163], and the availability of these high-throughput TRNGs can enable a wide range of new applications with improved security and privacy.…”
Section: Motivation and Goalmentioning
confidence: 99%
“…A widely-available, high-throughput, low-latency TRNG will enable all previously mentioned applications that rely on TRNGs, including improved security and privacy in most systems that are known to be vulnerable to attacks [90,115,162], as well as enable research that we may not anticipate at the moment. One such direction is using a one-time pad (i.e., a private key used to encode and decode only a single message) with quantum key distribution, which requires at least 4Gb/s of true random number generation throughput [34,94,154]. Many high-throughput TRNGs have been recently proposed [12,15,31,42,48,80,82,101,110,147,154,159,162,163], and the availability of these high-throughput TRNGs can enable a wide range of new applications with improved security and privacy.…”
Section: Motivation and Goalmentioning
confidence: 99%
“…When the quick response is needed, a positive short pulse can be applied to the source-drain electrode, the electron will recombine the trapped hole and reset the device, this will make rapid time response. The responsivity is as high as 4.8 × 10 6 A/W at 50 K, with 4.3 × 10 −14 W laser source power at 808 nm. Additionally, at room temperature, the detector's responsivity is 461A/W with 8.25 × 10 −12 W source power.…”
Section: Resultsmentioning
confidence: 88%
“…The MC simulations showed that the performance of the device could be optimized by reducing the horizontal trench width. The fabricated QD-ASN-FET-PD exhibits responsivity as high as 4.8 × 10 6 A/W at 50 K at 808 nm, which makes the weak light detection possible. This research provides a new method for optimizing a QDFET with high photocurrent response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…New protocols have recently been proposed that lift the requirement of operating a multiport and it is highly likely that future QDS test-beds will employ variations on these protocols. 35 Although 850 nm wavelength light has been successfully demonstrated in telecommunications optical fiber QKD systems [20][21][22][23]36,37 , suggesting that it could also be used successfully for QDS in the same type of fiber, true low loss long haul operation requires a system with a source wavelength that is around 1.3 μm or 1.55 μm.…”
Section: Conclusion and Discussionmentioning
confidence: 99%